Adsorption of Lead(II) Ions on Transcarpathian Clinoptilolite - V.I. Gomonaj; N.P. Golub; K. Yu. Szekeresh; P.V. Gomonaj; B. Charmas; R. Leboda (Adsorption Science & Technology)
The adsorption of lead(II) ions on the natural forms of Transcarpathian zeolite under static and dynamic conditions was investigated. Partial conversion of inactive calcium ions in the zeolite into relatively more mobile sodium or ammonium ions resulted in an increase in the adsorption of Pb 2+ ions. Similarly, partial removal of aluminium oxide from the zeolite changed its physicochemical properties and led to the maximum adsorption of lead(II) ions.